Expression and characterization of Carbohydrate Binding Module (CBM) from 38 Vibrio cholerae Non-O1 Sialidase - Shadariah, Mamat; Asmad, Kari; Nadiawati, Alias (2018)
Carbohydrate binding modules (CBMs) are discrete contiguous amino acid sequence within a carbohydrate-active enzyme which are non-catalytic modules that primarily exist to target parent enzyme to its substrate for efficient hydrolysis. Although many sialidase proteins have been identified from various pathogenic bacteria, only a few enzymes are commercially available which have been used for chemoenzymatic syntheses and therapeutics application. A gene encoding carbohydrate binding module (CBM) from Vibrio cholerae Non-O1 sialidase has been successfully cloned in E. coli BL21 (DE3). The CBM encodes for 174 amino acids from an open reading frame of 522 bp nucleotide sequences. The gene was successfully expressed solubly at 18˚C when induced with 1mM IPTG. Maximum protein expression was observed at 20 hours after post-induction time. For purification technique, an anionic denaturing detergent method was used using SDS and Sarkosyl with gradient affinity elution with imidazole. SDSPAGE analysis showed that the purified CBM protein exhibited a single band with molecular weight of 40 kDa. Biochemical characterization of the protein displayed optimum pH at 5.5 in 100 mM citrate buffer with the highest Tm value of 45.5 ºC. The protein was showed stable between pH 5.5-6.2 and able to retain its activity from 27-56 ˚C. From the analysis of metal ions and reagents, addition of Mn2+, Mg2+, 1% SDS, 1 M urea and 1% Triton managed to increase protein melting temperature to 59 ºC and 58.5 ºC respectively.